Regional Taxation in State Tax Reform - Kirk J. Stark (Washington University Journal of Law & Policy, 2019)
This article describes and evaluates a specific subset of state tax reforms—i.e., those involving regional approaches to funding subnational public goods. Reforms examined include those where policymakers devise new multijurisdictional fiscal arrangements to address regional objectives that conventional local governments, by virtue of their more limited geographic scope, are unlikely to tackle. As used in this article, the term “region” refers to a geographic area (1) constituting less than the entire jurisdiction of a state, and (2) encompassing more than one local government jurisdiction. A “regional tax” is therefore any tax (fee, assessment, etc.…) limited in its application to a geographic area so defined. A closely related policy is “regional tax base sharing”—i.e., the imposition of a tax on a base that is shared among several local jurisdictions, with the proceeds distributed among those localities. There are numerous instances of regional taxation and regional tax base sharing across the U.S. subnational public finance landscape. Some of these examples are familiar to a tax policy audience (such as the Minneapolis-St. Paul tax base sharing system), while others are less well known (such as the Denver Scientific and Cultural Facilities District). In most cases, the fiscal arrangement examined governs multiple counties spanning an entire metropolitan region. Following an evaluation of both successful and failed efforts at regional tax arrangements, the article considers possible extensions of these policies, discussing how regional taxes or tax base sharing might figure in tax reform efforts under consideration in California.
Keywords: Tax; SALT; State and local taxes; Tax law; Tax reform; Regional